Intra-access Pressure: Do We Really Need to Know? A Critical Review - Rehman, Abaid ur; Imtiaz, Salman (Pakistan Journal of Kidney Diseases, 2021)
Arteriovenous (AV) fistula and AV graft are considered superior to venous catheter access, remarkable success has been achieved in increasing prevalence of AV fistula. However, vascular access complications are common and result in increased hospitalization, mortality and expense. Guidelines suggest various methods to maintain patency of vascular access. Amongst these various methods used for vascular access monitoring and surveillance, intra-access pressure (PIA) is a simple tool which can be helpful in early detection and management of stenosis in vascular access. Intra-access pressure, although a very simple and quick method of vascular access evaluation, has a low diagnostic accuracy in prediction of vascular access stenosis as compared to other methods of access surveillance. We discuss here the physiology, methodology and the utility of intra-access pressure.